Determination of the genomic structure of homogentisate geranylgeranyl transferase gene of oil palm - Abdullah, Mohd Fauze Hazis (2015)
Elaeis guineensis originated from West Africa is the only species that was planted in the Malaysian plantation as a commercial oil palm. Since 1971, Malaysia has been the largest producer and exporter of oil palm. Oil palm is rich in vitamin E that consists of two major molecules which are tocopherols and tocotrienols. Oil palm is the richest source of tocotrienol. Homogentisate geranylgeranyl transferase (HGGT) is the enzyme that initiates tocotrienol synthesis in monocot seeds such as oil palm. The main objective of this study was to compare the genomic structure of HGGT gene of oil palm with other genomic structure of HGGT obtained from the previous study by using polymerase chain reaction (PCR) based method. Young leaves of oil palm were collected from the plantation area at Universiti Putra Malaysia, Serdang, Selangor, Malaysia and the leaves were extracted by using modified cetyltrimethyl ammonium bromide (CTAB). From this study, the genomic structure obtained was not exactly the same with the previous study due to the sequencing errors or the presence of introns in the sequence. From the alignment between genomic and the cDNA sequence, the introns that separate the coding sequence was able to be determined.